2019
DOI: 10.24940/ijird/2019/v8/i9/sep19024
|View full text |Cite
|
Sign up to set email alerts
|

Growth Performance, Blood Profile and Economic Efficiency of Layer Chicks Fed Diets Containing Graded Levels of Moringa Leaf Meal at Pre-Laying Phase

Abstract: A study was carried out to assess the effects of Moringa oleifera leaf meal (MOLM) inclusion in diets on the growth performance, blood profile and economic efficiency of layer chicks. Three hundred (300) one-day old layer chicks of ISA Brown breed were allocated to five dietary treatments and three replicates in a complete randomize design. Five different diets containing 0%, 3%, 6%, 9% and 12% MOLM were designated as treatments 1, 2, 3, 4 and 5. Treatment 1 was the control diet. Data collected were subjected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 2 publications
5
1
5
Order By: Relevance
“…However, this result is similar to previous studies conducted by Ogbe and Affiku 7 (27.44%) and Kwafo et al 17 (28.50%) but lower (30.65%) than those obtained by Mutayoba et al 18 . The crude protein value obtained confirms that moringa leaf meal is a good source of protein in the diets of birds.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, this result is similar to previous studies conducted by Ogbe and Affiku 7 (27.44%) and Kwafo et al 17 (28.50%) but lower (30.65%) than those obtained by Mutayoba et al 18 . The crude protein value obtained confirms that moringa leaf meal is a good source of protein in the diets of birds.…”
Section: Discussionsupporting
confidence: 92%
“…The crude protein value obtained confirms that moringa leaf meal is a good source of protein in the diets of birds. The value of crude fibre (13.34%) obtained in this study is lower (16.11%) than those reported by Kwafo et al 17 but higher (13.05 and 10.59%) than those reported by Kwafo et al 17 and Abbas et al 19 . The value of dry matter (89.64%) observed in the present study is lower than those obtained by Kwafo et al 17 (90.21) but higher than those reported by Kakengi et al 20 (86%).…”
Section: Discussioncontrasting
confidence: 75%
“…This value is higher than the value of 17.01 % and 23 % reported by Ogbe and Afiku [19] and Makkar and Becker [20] respectively. However, the result is comparable to the 27.44 % reported by Olugbemi et al [21] and 28.50 % reported by Kwafo et al [22] but lower than the 30.65 % obtained by Mutayoba et al [23]. The protein value (28.91) recorded in this study indicates that the nutrient content of the moringa gives an indication of its usefulness as an important feed resource for feeding Guinea fowls.…”
Section: Proximate Composition and Phytochemical Properties Of Moringa Leaf Mealsupporting
confidence: 80%
“…The crude fibre value obtained in this study is an indication that adding MOLM to the diet of Guinea fowls will not affect digestibility. The value for dry matter (89.64 %) was observed to be lower than the 90.21 obtained by Kwafo et al [22] but was higher than 86 % reported by Kakengi et al [26]. The values obtained for ether extracts (5.23 %), moisture (88.15 %), nitrogen free extracts (43.85 %) and total ash (7.13 %) were similar to values obtained in previous studies [19,21,25].…”
Section: Proximate Composition and Phytochemical Properties Of Moringa Leaf Mealcontrasting
confidence: 71%
See 1 more Smart Citation